Formação inicial interdisciplinar de professores de ciências e matemática : ressonâncias na educação básica - Trevisan, Andreia Cristina Rodrigues (2018)
This doctoral research has the purpose of problematizing the formation of the teacher who teaches Mathematics and Sciences, considering as object of study visions of graduates of the Licenciatura em Ciências Naturais e Matemática course (LCNM) (Degree in Natural Sciences and Mathematics) of Universidade Federal de Mato Grosso, University Campus of Sinop, about the initial formation and the practices experienced in the first years of teaching, in the basic school. The research aims to understand the visions of the graduates of this course about their initial formation and the practices lived in the first years of teaching, in the basic school, with respect to interdisciplinarity. The research has a qualitative research approach. Initially a questionnaire was applied to graduates of the course, for the production of data, this questionnaire was sent to 98 graduates, with the effective participation of 64. The analysis of the answers made it possible to identify some of the students' information about the course, and also to select those who were invited to the second moment of the research, in which these narrative interviews were carried out with these teachers, from which emerged elements that allowed a more accurate analysis of the research problem. The analysis of the interviews took place through the Discursive Textual Analysis (DTA), in which the data were synthesized in three categories that are related, namely: initial formation, interdisciplinarity and teaching pedagogical practice. The data indicate the relations between the experience lived by the interviewees in the initial training and the interdisciplinary perspective of the LCNM course, as well as make it possible to understand the interdisciplinary practices mediated by teachers/graduates, research collaborators, in basic education. It was possible to observe that the interdisciplinarity manifests itself in the practice of these teachers/graduates from activities with interdisciplinary approaches, mainly in situations that involve the work with themed. The development of these activities involves both institutionalized actions by the schools and personal actions of the teachers, when approaching certain school contents. The research shows that sometimes interdisciplinarity has been confused with multidisciplinarity. There are also indications of challenges to be faced in establishing interdisciplinary practices in teaching, such as inflexibility of the curriculum, school time and difficulty in establishing collective work. Finally, it is concluded that the initial interdisciplinary training has the potential to foment interdisciplinary approaches in pedagogical practice in basic education, and that this is linked to new postures and understandings about and in teacher training.